THE EFFECTIVENESS OF THE HUMBLE LEADERSHIP PRACTICED BY THE HEADS OF FOOTBALL CLUBS IN NINEVEH GOVERNORATE IN ACHIEVING EMOTIONAL SOLIDARITY FROM THE POINT OF VIEW OF MEMBERS OF ITS ADMINISTRATIVE BOARD MEMBERS - Qassem Abdel Hafedh Mahmoud Hussein (Proximus Journal Publishing, 2024)
Constructing two scales to measure the level of humble leadership among the heads of football clubs in Nineveh Governorate from the point of view of members of the administrative bodies, and emotional exhaustion among the members of its administrative bodies from their point of view. - Identifying the level of humble leadership of football club presidents in Nineveh Governorate from the point of view of members of its administrative bodies
Keywords: members; Identifying; administrative